Sugarcane leaf litter biomass and its effects on increasing sugarcane drought stress tolerance and reducing CO₂ emissions - Kalbuadi, Donny Nugroho; Siswanto, Siswanto; Widiastuti, Happy (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Burning biomass on sugarcane plantations can lead to pollution (CO₂ emissions) and degradation in soil properties. Adopting non-burning technology can increase the value of biomass by applying it directly to the soil, although this may result in nutrient immobilization, which can hinder optimal plant growth due to high lignin and cellulose content or high CN ratio. On the contrary, composting waste with a decomposer will boost plant nutrient availability and enhance other soil characteristics. This research was aimed to assess the effect of several types of sugarcane organic matter on improving soil characteristics, growth of sugarcane and the CO₂ emissions. The study was conducted using a Completely Randomized Factorial Design with two factors: type of organic matter (control, fresh litter and compost of sugarcane biomass) and level of drought stress (100, 75, 50 and 25%). Incubation occurred over 16 weeks, divided into two phases of 8 weeks each. The results showed that the application of organic materials in the form of compost could reduce water loss caused by environmental heat and sugarcane growing process. Furthermore, compost application improved soil chemical and biological properties by increasing soil pH, total nitrogen (N), total phosphate (P), total potassium (K), and the total microbial population, although differences were not significant compared to the control. Additionally, applying organic matter in the form of compost or litter helped suppress or reduce emissions, with compost treatment proving more effective than litter in reducing CO₂ emissions.